Analisis Yuridis Tujuan dan Kewenangan Otoritas Jasa Keuangan (OJK) dalam Lembaga Perbankan di Indonesia - Yulia Hesti (PRANATA HUKUM, 2018)
The industry of the financial services or banking sector is demanded to be constantly stable, that is healthy, transparent and well managed. Such banking conditions can build consumers to continue to actively engage in transactions. However, as time goes by the development of the financial services industry in Indonesia is increasing and the cross-sectoral problems of the financial services industry are increasingly in need of reform in the field of banking law, then the Financial Services Authority is formed as an institution that will replace Bank Indonesia in the supervision of banks and supervise institutions other finance. OJK in its formation has several objectives to carry out supervision, especially in the financial services sector. Pursuant to Article 4 of the OJK Law, OJK was formed with the aim that all activities within the financial services sector: (a) be organized regularly, fairly, transparently and accountably; (b) Able to realize a financial system that grows sustainably and stably; and (c) Able to protect the interests of consumers and society. Based on its authority, the OJK carries out the task of regulating and supervising the banking sector in accordance with its functions as stipulated in Article 5 of the OJK Law which functions to organize an integrated regulation and supervision system for all activities within the financial services sector. With the presence of OJK in supervision, banking and other financial institutions can create harmonious regulations so as to protect consumer rights.